Morphologic features of the "Athlete`s Heart" in children: A contemporary review - Rowland, T. (Pediatric Exercise Science, 2016)
Recognizing the cardiac features of athletically trained children bears importance for health care providers and exercise physiologists alike. This literature review reveals that ventricular enlargement and/or hypertrophy are commonly observed in studies of pre- and early-adolescent endurance athletes, yet the magnitude of these features is less than that described in adult athletes. Moreover, the upper range of values in child athletes is sufficiently small that clinical confusion with findings mimicking those in individuals with heart disease should not be expected to occur. In contrast to sex differences in the "athlete`s heart" in adults, cardiac structural findings in child athletes are similar in males and females. The extent that cardiac features observed in trained child athletes reflect a response to training or are influenced by genetic preselection remains uncertain.